Application of diffusion tensor imaging of the facial nerve in preoperative planning for large vestibular schwannoma: a systematic review - Bubeníková, Adéla; Vlasák, Aleš; Fík, Zdeněk; Sedlák, Vojtěch; Tesařová, Michaela; Bradáč, Ondřej (Neurosurgical review, 2023)
The accurate identification and preservation of the facial nerve (FN) during vestibular schwannoma (VS) surgery is crucial for maintaining facial function. Investigating the application of diffusion tensor imaging (DTI) in preoperative planning for large VS surgery is provided. PubMed, Cochrane Library, Science Direct, ISI Web of Science, Embase, and additional sources were searched to identify cohort studies about the preoperative DTI usage for the FN tracking before large VS (≥ 2.5 cm) surgery published between 1990 and 2023. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed; the Newcastle-Ottawa Scale was used to assess the risk of bias and to evaluate limitations based on selection/outcome biases. A total of 8 publications yielding 149 VS (mean size 3.66 ± 0.81 cm) were included. Surgical concordance with preoperative DTI FN tracking was 91.67% (range 85-100%). Overall DTI reliability was 88.89% (range 81.81-95.83%). Larger tumor size predicted either DTI inaccurate finding or complete DTI failure (p = 0.001). VS size above > 3.5 cm was associated with a higher risk of DTI failure (p = 0.022), with a higher risk of inaccurate DTI finding preoperatively (p = 0.033), and with a higher House-Brackman score postoperatively (p = 0.007). Application of DTI in larger VS surgery is a valuable FN identification along with electrophysiological monitoring and neuronavigation, therefore also in its preservation and in lowering risk of complications. DTI represents a valuable adjunct to electrophysiological monitoring and neuronavigation in FN identification, applicable not only for smaller, but also larger VS.
Keywords: Reproducibility of Results; nervus facialis; Facial Nerve Injuries; vestibulární schwannom; lidé; zobrazování difuzních tenzorů; reprodukovatelnost výsledků; poranění nervus facialis; Facial Nerve; Diffusion Tensor Imaging; Neuroma, Acoustic; Humans